Brotherhood of the flying coffin : the glider pilots of World War II - McGaugh, Scott (Osprey Publishing, 2023)
"This book distills war down to individual young men climbing into defenseless gliders made of plywood, ready to trust the towing aircraft that would pull them into enemy territory by a single cable wrapped with a telephone wire. Based on their after-action reports, journals, oral histories, photos and letters home, The Brotherhood of the Flying Coffin reveals every terrifying minute of their missions. They were all volunteers, for a specialized duty that their own government projected would have a 50 percent casualty rate. None faltered. In every major European invasion of the war they led the way. They landed their gliders ahead of the troops who stormed Omaha Beach, and sometimes miles ahead of the paratroopers bound for the far side of the Rhine River in Germany itself. From there, they had to hold their positions. They delivered medical teams, supplies and gasoline to troops surrounded in the Battle of the Bulge, ahead even of Patton's famous supply truck convoy. These all-volunteer glider pilots played a pivotal role in liberating the West from tyranny, from the day the Allies invaded Occupied Europe to the day Germany finally surrendered. Yet the story of these anonymous heroes is virtually unknown. Here their story is told in full - a story which epitomizes courage, dedication and sacrifice."--